PENGARUH KOMUNIKASI TIM REKAM MEDIS DAN LOKET TERHADAP TINGKAT KECEPATAN PELAYANAN DI PUSKESMAS SESELA - Lili Octaviani Lili octaviani; Syatriawan Perdana Putra (Nusadaya Journal of Multidiciplinary Studies, 2024)
This study aims to (1) Whether there is an influence between X and Y in the Sesela Health Center. This research was carried out for 3 months starting from March to June 2023 using the Correlational Studies method. The number of respondents as a sample is 100 people. The data collected in the analysis used a simple regression analysis. The results of this study show that (1) effective communication between the Medical Record team and the Counter has a significant impact on the level of service speed at the Sesele Health Center. The clarity of information conveyed between the two teams has proven to be a key factor in improving service efficiency. Respondents who felt that the information they received were easy to understand tended to rate the speed of service, indicating that clear instructions can reduce the time it takes to deliver services to patients.